Decolonizing Diasporas Radical Mappings of Afro-Atlantic Literature - Figueroa-Vásquez, Yomaira (Northwestern University Press, 2020)
Decolonizing Diasporas proposes a new way to read the literary and cultural productions of the Afro-Atlantic. Mapping literature from Spanish-speaking Sub-Saharan African and Afro-Latinx Caribbean diasporas, Figueroa-Vásquez argues that the works of diasporic writers and artists offer ways of imagining new worldviews which dismantle the logics of colonial modernity. Utilizing women of color feminisms and decolonial theory as frameworks, Figueroa-Vásquez analyzes artists from the peripheries of their respective diasporas to reveal the thematic, conceptual, and liberatory tools that they offer when read in relation to one another. Decolonizing Diasporas examines how themes of intimacy, witnessing, dispossession, reparations, and futurities are remapped in these works by tracing interlocking structures of oppression. This study serves as a primer for approaching questions of home, diaspora, belonging, and justice, by centering the cultural productions of peoples of African descent.